2005
DOI: 10.1111/j.1463-1326.2005.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of glycaemic control on ocular complications of Spontaneously Diabetic Torii rat

Abstract: These findings indicate that ocular complications of SDT rats are caused by hyperglycaemia. The features of SDT rats indicate their usefulness for the future study of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 30 publications
(34 reference statements)
2
58
0
Order By: Relevance
“…Since the peak latency of SDT fatty rats on ERG was retarded at 16 and 24 week of age, functional abnormality of the retina may have occurred. The peak latency of the SDT normal rat showed a prolongation at 44 weeks of age [16]. There was no difference in the peak latency at 32 weeks of age between the SDT normal rat group and the SDT fatty rat group because of the prolongation of the peak latency in the SDT normal rat group.…”
Section: A B C Dmentioning
confidence: 76%
See 3 more Smart Citations
“…Since the peak latency of SDT fatty rats on ERG was retarded at 16 and 24 week of age, functional abnormality of the retina may have occurred. The peak latency of the SDT normal rat showed a prolongation at 44 weeks of age [16]. There was no difference in the peak latency at 32 weeks of age between the SDT normal rat group and the SDT fatty rat group because of the prolongation of the peak latency in the SDT normal rat group.…”
Section: A B C Dmentioning
confidence: 76%
“…Body weight, food intake, biochemical parameters, and renal parameters were evaluated at 4,6,8,16,24, and 32 weeks of age. Blood samples were collected from the tail vein of rats.…”
Section: Biological Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…SDT rats also develop ocular complications (cataract and retinopathy) and nephropathy from about 40 weeks of age [24]. Sasase et al have reported that the lesions in SDT rats are induced by hyperglycemia because an improvement is observed following continuous subcutaneous insulin administration [14,20]. Therefore, the SDT rat is expected to be useful as a new animal model of diabetes-associated complications such as retinopathy and nephropathy.…”
Section: Introductionmentioning
confidence: 99%